2011
DOI: 10.5194/acp-11-6773-2011
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol flux measurements above a mixed forest at Borden, Ontario

Abstract: Abstract. Aerosol fluxes were measured above a mixed forest by Eddy Covariance (EC) with a Fast Mobility Particle Sizer (FMPS) at the Borden Forest Research Station in Ontario, Canada between 13 July and 12 August 2009. Chemically speciated flux measurements were made at a height of 29 m at the same location between 19 July and 2 August, 2006 using a Quadrupole Aerosol Mass Spectrometer (Q-AMS). The Q-AMS measured an average sulphate deposition velocity of 0.3 mm s −1 and an average nitrate deposition velocity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…[], who pointed out that this downward flux can lead to overestimations of the dry‐deposition velocity of nitrate. Several other studies also measured large apparent deposition fluxes of aerosol nitrate and ammonium with an aerosol mass spectrometer eddy‐covariance flux system and by measuring concentration gradients [ Fowler et al ., ; Gordon et al ., ; Nemitz et al ., ; Wolff et al ., ; Wyers and Duyzer , ]. We have confirmed that flux measurements of total nitrate are more suitable for estimating deposition velocities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[], who pointed out that this downward flux can lead to overestimations of the dry‐deposition velocity of nitrate. Several other studies also measured large apparent deposition fluxes of aerosol nitrate and ammonium with an aerosol mass spectrometer eddy‐covariance flux system and by measuring concentration gradients [ Fowler et al ., ; Gordon et al ., ; Nemitz et al ., ; Wolff et al ., ; Wyers and Duyzer , ]. We have confirmed that flux measurements of total nitrate are more suitable for estimating deposition velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, experimental confirmation needs fast measurements (more than 1 Hz) of the nitrate mixing ratio, which is technically challenging [ Crosier et al ., ]. Such fast measurements are normally only performed for specific flux studies at the surface [ Farmer et al ., ; Fowler et al ., ; Gordon et al ., ; Nemitz et al ., ]. Our simulations further predict that gas‐aerosol partitioning induces a downward flux of nitrate in the convective boundary layer.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, measurements show that during nucleation events particle concentrations are larger at higher heights than in the forest canopy, suggesting that the canopy is not a source region for nucleation (Gordon et al 2011;Pryor et al 2008aPryor et al , 2009). There is the general understanding that there is no effective primary source of submicron particles from vegetation, except for the release of some small PBAP.…”
Section: Interpretation Of Emission and Fast Deposition Fluxesmentioning
confidence: 99%
“…However, these surfaces are usually considered unrepresentative of vegetation. Special fast data acquisition modes have been developed (Crosier et al 2007;Kimmel et al 2011) that allow its application for eddy-covariance flux measurements (Gordon et al 2011;Nemitz et al 2008;Thomas 2007;Zalakeviciute et al 2012). Duyzer 1994;Wyers and Duyzer 1997), and sulphate fluxes were measured by eddy-covariance with a fast chemiluminescence detector as early as the 1980s (Wesely et al 1985b).…”
Section: Aerosol Chemical Componentsmentioning
confidence: 99%
“…A combination of fastresponse particle sizers and an eddy covariance system have been used to study vertical transport of atmospheric particles (Gordon et al, 2011). The calculated vertical exchange fluxes of atmospheric particles of different sizes are always positive; however, this is practically impossible in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%